Scenario-based comparative assessment of potential future electricity systems – A new methodological approach using Germany in 2050 as an example. (1st June 2016) - Lunz, Benedikt; Stöcker, Philipp; Eckstein, Sascha; Nebel, Arjuna; Samadi, Sascha; Erlach, Berit; Fischedick, Manfred; Elsner, Peter; Sauer, Dirk Uwe
Graphical abstract: Highlights: Method for evaluation and comparison of potential future electricity systems. Newly developed algorithm defines the mix of technologies providing flexibility. Algorithm has a very short runtime allowing for comprehensive parameter variations. Abstract: In this paper a new method for the evaluation and comparison of potential future electricity systems is presented. The German electricity system in the year 2050 is used as an example. Based on a comprehensive scenario analysis defining a corridor for possible shares of fluctuating renewable energy sources (FRES) residual loads are calculated in a unified manner. The share of electricity from PV and wind power plants in Germany in the year 2050 is in a range of 42–122% and the load demand has a bandwidth of around 460–750 TWh. The residual loads are input for an algorithm that defines a supplementary mix of technologies providing flexibility to the system. The overall system layout guarantees the balance of generation and demand at all times. Due to the fact that the same method for residual load calculation and mixture of technologies is applied for all scenarios, a good comparability is guaranteed and we are able to identify key characteristics for future developments. The unique feature of the new algorithms presented here is the very fast calculation for a year-long simulation with hourly or shorter time steps taking into account the state of charge or availability of all storage and flexibility technologies. This allows an analysis of many different scenarios on a macro-economic level, variation of input parameters can easily be done, and extensive sensitivity analysis is possible. Furthermore different shares of FRES, CO2 -emission targets, interest rates or social acceptance of certain technologies can be included. The capabilities of the method are demonstrated by an analysis of potential German power system layouts with a base scenario of 90% CO2 -reduction target compared to 1990 and by the identification of different options for a power sector with a high degree of decarbonisation. The approach also aims at a very high level of transparency both regarding the algorithms and regarding the input parameters of the different technologies taken into account. Therefore this paper also gives a comprehensive and complete overview on the technology parameters used. The forecast on all technologies for the year 2050 regarding technical and economic parameters was made in a comprehensive consultation process with more than 100 experts representing academia and industry working on all different technologies. An extensive analysis of options for the design of potential German energy supply systems in 2050 based on the presented methodology will be published in a follow-up paper.